Problematizations in Assisted Dying Discourse: Testing the “What's the Problem Represented to Be?” (WPR) Method for Critical Health Communication Research - Pringle, Wendy (Frontiers in Communication, 2019)
In this paper I test the methodological potential of a set of six questions, called the ‘What’s the Problem Represented to be?,’ or WPR approach, borrowed from the field of discursive policy analysis (Bacchi 2012) for doing critical health communication (CHC) research. WPR is generative for critical health researchers because it shares the goal of challenging implicit and explicit causality and correlation within discourse. I apply these questions to examine the case of legalized medical assistance in dying (MAiD) in Canada, arguing that their simplicity and capaciousness facilitate critical responses to care disparities. This particular case is edifying for CHC researchers, because ideals of good living, ‘dignified’ death, and the role of medicine are all crystallized within legal, media, and medical discourse on assisted dying. Debating what death can or should look like depends on a clearer understanding of how the logics of embodied difference (especially ability, race, and gender) are always already stacking the odds against equal political participation in, and access to health. The WPR approach flips the ‘proper objects’ of health-centered critical research, beginning by scrutinizing proposed solutions in order to rethink the problems implicit therein. Asking such questions as “How has this representation of the ‘problem’ come about?”, “What effects are produced by this representation of the ‘problem’?” and “How has it been (or could it be) questioned, disrupted and replaced?” productively situates the researcher between the discursive practices governing health and health care praxis itself. Ultimately, I argue that the WPR method encapsulates some of the best critical perspectives from the corpus of CHC research praxis, making it a helpful tool for advancing health communication research.